Enhancing Safe Usage of Nonsteroidal Anti-inflammatory Drugs - Nawaf Awadh Almatrafi Munif Awadh Almatrafi Ahlam khalid Al-Mutairi Manal Ghazai Al-Anzi Abdullah Ghazai Al-Anzi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Assessing the Impact of Audit/Feedback and Educational Resources on Adherence to Monitoring Recommendations for Nonsteroidal Anti-inflammatory Drug (NSAID) Safety. Study Design: A retrospective study Methods: Physicians commonly prescribing NSAIDs within a large managed care organization were selected into either a control or intervention group (receiving audit/feedback with peer-derived benchmarks and continuing medical education). Medical records were reviewed before and after a 10-month intervention period to evaluate adherence to laboratory monitoring and cytoprotective agent recommendations. General estimating equations were employed to adjust for patient clustering. Results: Among the initially selected 101 physicians, 85 remained eligible post-intervention (comprising 38 internists, 36 family physicians, and 11 rheumatologists). The mean percent change in performance between participants regarding complete blood count (CBC) monitoring was 16% versus 10%, for creatinine monitoring was 0% versus 17%, and for the use of cytoprotective agents was -3% versus -1%. However, these changes were not statistically significant. Factors such as rheumatology specialty, number of NSAID prescriptions and physician visits, and patient risk factors for NSAID-related toxicity exhibited stronger associations with improved safety practices compared to the intervention itself. Conclusions: Audit/feedback and educational materials did not demonstrate a significant impact on improving NSAID-related safety practices. Potential contributing factors include high baseline performance, dilution of intervention effects by case mix and provider factors, nonreceipt of intervention materials, and diverse indications for laboratory tests